2020
DOI: 10.1242/jcs.238527
|View full text |Cite
|
Sign up to set email alerts
|

Lamin is essential for nuclear localization of the GPI synthesis enzyme PIG-B and GPI-anchored protein production in Drosophila

Abstract: Membrane lipid biosynthesis is a complex process that occurs in various intracellular compartments. In Drosophila, phosphatidylinositol glycan-B (PIG-B), which catalyzes addition of the third mannose in glycosylphosphatidylinositol (GPI), localizes to the nuclear envelope (NE). Although this NE localization is essential for Drosophila development, the underlying molecular mechanism remains unknown. To elucidate this mechanism, we identified PIG-Binteracting proteins by performing immunoprecipitation followed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 46 publications
(57 reference statements)
1
2
0
Order By: Relevance
“…It has recently been reported that oxidoreductases and lipid synthases, which play a role in regulating cell growth and survival, are also localized in the NL ( Cheng et al, 2023 ), and their localization and function may be abnormal in PIGB mutants. We previously reported that PIGB binds to Lamin Dm0 ( Yamamoto-Hino et al, 2020 ), and overexpression of PIGB in this study affected the localization of Lamin Dm0. These results suggest that disruption of the NL in PIGB 13 is due to the impaired distribution of Lamin Dm0.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…It has recently been reported that oxidoreductases and lipid synthases, which play a role in regulating cell growth and survival, are also localized in the NL ( Cheng et al, 2023 ), and their localization and function may be abnormal in PIGB mutants. We previously reported that PIGB binds to Lamin Dm0 ( Yamamoto-Hino et al, 2020 ), and overexpression of PIGB in this study affected the localization of Lamin Dm0. These results suggest that disruption of the NL in PIGB 13 is due to the impaired distribution of Lamin Dm0.…”
Section: Discussionsupporting
confidence: 59%
“…Moreover, the C-terminal Ig-fold regions of lamins are observed at 20 nm intervals on both sides of filaments ( Turgay et al, 2017 ). We have reported that the Ig-fold domain of Lamin Dm0 mainly binds to PIGB, while the other domains may slightly contribute to the association with PIGB ( Yamamoto-Hino et al, 2020 ). It is possible that PIGB acts as a support for Lamin Dm0 to spread the network homogenously with proper spacing via its C-terminal Ig-fold region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation